Reconstruction of severely atrophied alveolar ridges with calvarial onlay bone grafts and dental implants - Mertens, Christian; Steveling, Helmut; Seeberger, Robin; Hoffmann, Jürgen; Freier, Kolja (Clinical implant dentistry and related research, 2013)
Objective: Severely atrophied alveolar ridges are most commonly reconstructed with free autologous bone grafts from the iliac crest. The use of these grafts, however, is frequently associated with bone resorption as possible late complication after implant surgery and prosthetic loading. Other donor sites, especially intraoral donor sites, show limited availability. The aim of this present study was to evaluate the clinical and radiographical outcome of alveolar ridge reconstruction with bone from the calvarium and subsequent implant rehabilitation. Patients and Methods: Reconstruction was performed by using calvarial split grafts in case of severe and complex alveolar ridge defects induced by trauma or bone atrophy. Fifteen patients were treated at 19 different intraoral recipient sites (15 sites in the maxilla, four in the mandible). Autologous block grafts were used for combined vertical and horizontal grafting. After a 3-month healing period, patients received dental implants. A total of 99 dental implants (OsseoSpeed™, Astra Tech AB, Mölndal, Sweden) were inserted and left to heal in a submerged position for 3 months before the prosthetic implant-based rehabilitation was performed. Results: No donor site complications occurred during or after surgery. At the intraoral recipient sites two infections occurred, leading to partial loss of the grafts. Implant placement, however, was possible in all cases. Two of 99 implants were lost in two patients prior to prosthetic loading. Patients were followed up clinically and radiographically for an average observation period of 28 months. Implant survival rate and success rates were 97.85 and 95.7%, respectively, and a minimal marginal bone loss was documented. Discussion: The low morbidity at the donor sites and the good marginal bone stability in the reconstructed regions indicate that calvarial bone grafts represent a viable treatment alternative to grafts from the iliac crest.